O leite de búfala - Ricci, Gisele Dela [UNESP]; Domingues, Paulo Francisco [UNESP] (My University, 2012)
Milk production stands out as one of the main skills of buffaloes, and is considered to be very important in several countries. The market for buffalo milk products is fast growing in Brazil. These products, specially the Mozzarella and the Ricotta cheese, are acquired not only because of their particular taste, but also for their nutritional qualities. The buffaloes are considered less susceptible to mastitis than cows, even though the microorganisms involved in the infection are similar. This article describes several aspects of buffalo milk, particularly production, physico-chemical and microbiological characteristics.

A produção de leite se destaca como uma das principais aptidões das búfalas e é considerada de grande importância em vários paí- ses. O mercado para os derivados do leite de búfala está em franca expansão no Brasil. Esses produtos, principalmente a muçarela e a ricota, são procurados não só por seu sabor característico, mas também por suas qualidades nutricionais. As búfalas são consideradas menos susceptíveis à mastite do que as vacas, embora os microrganismos envolvidos na infecção sejam semelhantes. Este artigo aborda aspectos relacionados ao leite de búfala, destacandose produção, características físico-químicas e microbiológicas.
The buffalo milk
Keywords: Buffaloes; Milk; Production; Búfalas; Leite; Produção